The use of ICTs in IBE as a tool for the revitalization of Quechua language - Herrera Corahua, Juan Bautista (2022)
The active and interactive means of ICT (Information and Communication Technology), such as the social network WhatsApp and Facebook, offer tools to revitalize the Quechua language, thus favoring and motivating its practice. The objective of the study is to describe how the use of ICT allows revitalization of the Quechua language of the students of the Capilla annex, period 2020-2021. To this end, a psycholinguistic and sociolinguistic characterization was carried out to recognize the level of mastery and linguistic scenario of the students; then activities were proposed to create materials in Quechua with the use of ICT. The results of the psycholinguistic diagnosis show that all students have Spanish as their L1, and 25% of them have Quechua as their L2 or heritage language. Likewise, the sociolinguistic diagnosis shows that communication in the school environment and within the nuclear family is in Spanish and the practice of Quechua occurs when the children interact with their Quechua-speaking relatives. In conclusion, the revitalization of Quechua using ICTs requires the appropriate use of active media, and the creation of audio and video, including daily or cultural activities of the community.